A Critical Review of the Standard Empanelment Process and Identifying Modifications for Improvement. (September 2015) - Gaikwad, Sandip; Patil, Bharat; Kasat, Sachhin; Bhardwaj, Geeta; Yadav, Pravin; Shukla, Kasturi
Objective: To study the standard empanelment process for Provider Management (PM) Department, MD India Healthcare Services (third party administrator (TPA)) Private Limited; to identify improvements in the empanelment process. Methods: This was a cross-sectional study conducted through quantitative and qualitative methods. The study was conducted at the head office of MD India Healthcare Services (TPA) Private Limited, Vadgaonsheri, Nagar Road, Pune. Results: In addition to the standard criteria of MD India (MDI) for empanelment of hospitals, there are specific criteria for new empanelment which include requirement of the network hospital in that location like a registered hospital with minimum 25 bed strength and hospital having good non-cashless business. For new hospitals to be empanelled, there are two ways: either the hospital approaches the head office/service branch of TPA or the TPA approaches the hospital for empanelment. Our study identifies some modification to improve this empanelment process. Conclusions: The aim of TPA is to facilitate insurance process to provide best quality service to patients. The modifications identified in our study will improve the process in many ways.